Macrominerals and Trace Minerals in Commercial Infant Formulas Marketed in Brazil: Compliance With Established Minimum and Maximum Requirements, Label Statements, and Estimated Daily Intake - Almeida, Cristine Couto; Baião, Diego dos Santos; Rodrigues, Paloma de Almeida; Saint'Pierre, Tatiana Dillenburg; Hauser-Davis, Rachel Ann; Leandro, Katia Christina; Paschoalin, Vania Margaret Flosi; Costa, Marion Pereira da; Conte-Junior, Carlos Adam (Frontiers in Nutrition, 2022)
Infant formulas are the main nutritional source for infants when breastfeeding is not possible or recommended. The daily need for specific nutrients, such as essential minerals, in early stages of a child's life is high because of rapid infant growth and development, which impose metabolic flux increases on these pathways to support growth, physical activity, and defense against infections. In this context, this research aimed to determine macromineral and trace mineral contents in starting (phase 1) and follow-up (phase 2) infant formulas marketed in Brazil (n = 30) by inductively coupled plasma-mass spectrometry, calculate estimated daily intakes, and compare them to reference values regarding adequate intake and tolerable upper intake levels. The highest concentrations of macrominerals were observed in Ca, K, P, and Na, and trace minerals in Fe, Zn, Mn, and Cu. Certain homogeneity only to trace mineral contents was observed when analyzing inter-batch values from same manufacturers. In general, all phase 1 and phase 2 infant formula brands and batches met or exceeded Fe, Zn, Cu, Mo, and Se contents when compared to maximum limits established by Codex Alimentarius. In addition, Zn contents in eight phase 1 and in four phase 2 infant formulas were above the contents established by the tolerable upper intake level for children aged 0–6 and/or 7–12 months, respectively. These findings highlight the need to expand regular infant formula inspection concerning nutritional quality, as some composition aspects of these foods must be improved to follow international guidelines, since ideal requirements for infant formula composition, quality, and safety interfere in child development and adult health.